Synthesis and fluorine-18 radiolabeling of a phospholipid as a PET imaging agent for prostate cancer - Kwan, Kim H. (Nucl Med Biol, 2020)
INTRODUCTION: Altered lipid metabolism and subsequent changes in cellular lipid composition have been observed in prostate cancer cells, are associated with poor clinical outcome, and are promising targets for metabolic therapies. This study reports for the first time on the synthesis of a phospholipid radiotracer based on the phospholipid 1,2-didocosahexaenoyl-sn-glycero-3-phosphocholine (PC44:12) to allow tracking of polyunsaturated lipid tumor uptake via PET imaging. This tracer may aid in the development of strategies to modulate response to therapies targeting lipid metabolism in prostate cancer. METHODS: Lipidomics analysis of prostate tumor explants and LNCaP tumor cells were used to identify PC44:12 as a potential phospholipid candidate for radiotracer development. Synthesis of phosphocholine precursor and non-radioactive standard were optimised using click chemistry. The biodistribution of a fluorine-18 labeled analogue, N-{[4-(2-[(18)F]fluoroethyl)-2,3,4-triazol-1-yl]methyl}-1,2-didocosahexaenoyl-sn-glycero-3-phosphocholine ([(18)F]2) was determined in LNCaP prostate tumor-bearing NOD SCID gamma mice by ex vivo biodistribution and PET imaging studies and compared to biodistribution of [(18)F]fluoromethylcholine. RESULTS: [(18)F]2 was produced with a decay-corrected yield of 17.8 ± 3.7 % and an average radiochemical purity of 97.00 ± 0.89% (n = 6). Molar activity was 85.1 ± 3.45 GBq/µmol (2300 ± 93 mCi/µmol) and the total synthesis time was 2 hours. Ex vivo biodistribution data demonstrated high liver uptake (41.1 ± 9.2 %ID/g) and high splenic uptake (10.9 ± 9.1 %ID/g) 50 minutes post-injection. Ex vivo biodistribution showed low absolute tumor uptake of [(18)F]2 (0.8 ± 0.3 %ID/g). However, dynamic PET imaging demonstrated an increase over time of the relative tumor-to-muscle ratio with a peak of 2.8 ± 0.5 reached 1 hour post-injection. In contrast, dynamic PET of [(18)F]fluoromethylcholine demonstrated no increase in tumor-to-muscle ratios due to an increase in both tumor and muscle over time. Absolute uptake of [(18)F]fluoromethylcholine was higher and peaked at 60 minutes post injection (2.25 ± 0.29 %ID/g) compared to [(18)F]2 (1.44 ± 0.06 %ID/g) during the 1 hour dynamic scan period. CONCLUSIONS AND ADVANCES IN KNOWLEDGE: This study demonstrates the ability to radiolabel phospholipids and indicates the potential to monitor the in vivo distribution of phospholipids using fluorine-18 based PET.